Efficient Stacked OLED processed by Organic Vapor Phase Deposition (OVPD). Issue 1788 (2015) - Brast, M.; Axmann, S.; Slawinski, M.; Weingarten, M.; Lindla, F.; Bösing, M.; Heuken, M.; Vescan, A.; Kalisch, H.
ABSTRACT: The development of efficient large-area organic light emitting diodes (OLED) requires reliable and easily processable charge generation layers (CGL) with low excess voltage drop and high optical transparency. OVPD offers the advantage of a precise control of layer morphology, composition and thickness and is a powerful method for the deposition of advanced OLED designs. In this work, electrical doping of organic semiconductors using OVPD is investigated and applied to stacked OLED utilizing inorganic/organic CGL. The organic p-type dopant NDP-9 of Novaled GmbH is used for doping the hole transport material N, N'-diphenyl-N, N'-bis(1-naphthylphenyl)-1, 1'-biphenyl-4, 4'-diamine (α-NPD) in an AIXTRON OVPD tool. A doping concentration of 8 vol.% of NDP-9 in α-NPD is found optimal for hole injection as well as conductivity. This dopant concentration was employed in CGL with the structure: electron transport material/LiF/Al/α-NPD:8 vol.% NDP-9. External quantum efficiencies (EQE) of 15%, 35% and 50% and luminous efficiencies of 37 lm/W, 45 lm/W and 45 lm/W at 1000 cd/m 2 are demonstrated for single, double- and triple-unit green phosphorescent OLED, respectively.